DIVERSITY OF FERNS (PTERIDOPHYTA) WITH DIFFERENT VEGETATION IN FOREST AREAS BUKUM VILLAGE, SIBOLANGIT SUB-DISTRICT - Wira Hariati Simbolon; Melfa Aisyah Hutasuhut; Zahratul Idami (Universitas Islam Negeri Ar-Raniry, 2023)
Ferns or Pteridophyta are lower plants from the Cryptogamae division, which can be distinguished between roots, leaves, and stems. Ferns have great ecological importance, namely as understory plants that contribute to the long-term sustainability of forest ecosystems by mixing soil litter, as ground cover vegetation, as producers in the food chain, and as one of the pioneer plants in the succession of forest ecosystems. This study aims to determine the species, diversity index, and distribution pattern of ferns based on different vegetation in the Forest Area of Bukum Village, Sibolangit District, North Sumatra. The method used in this research is an exploratory survey method with a purposive sampling technique. The results of this study were 39 species found in the Forest Area of Bukum Village, 21 species in the watershed vegetation, 16 species in the Coffee Garden vegetation, and 14 species in the Primary Forest vegetation. The diversity index in the watershed vegetation is 2.32, the coffee plantation is 2.02, and the primary forest is 1.86. Based on the results of the diversity index, it shows that the diversity of ferns in the Forest area of Bukum Village is classified as moderate so the community is said to be stable. The Morisita index on the river flow vegetation is 1.43, the coffee garden vegetation is 2.13, and the primary forest vegetation is 2.05. The results of the Morisita index from each vegetation indicate that the distribution pattern of ferns in the Forest Area of Bukum Village is grouped because the environmental conditions required by ferns are not uniform.